Which antiarrhythmic drug to choose after electrical cardioversion: A study on non-valvular atrial fibrillation patients - Gwag, Hye Bin (PLoS One, 2018)
The relative efficacy of antiarrhythmic drugs (AADs) after electrical cardioversion are not well established. This study aimed to investigate the efficacies of different AADs for maintaining sinus rhythm (SR) after electrical cardioversion for atrial fibrillation (AF). We selected patients from a retrospective registry including patients admitted for cardioversion between January 2012 and June 2016. The primary outcome was time to AF recurrence during the first year after cardioversion. The secondary outcomes included AF recurrence within 1 month, and first readmission due to heart failure, stroke, or additional non-pharmacological rhythm control. A total of 265 patients were divided into the 4 groups according to AAD type: flecainide (n = 33), propafenone (n = 64), amiodarone (n = 128), and dronedarone (n = 40). During the first year after cardioversion, the AF recurrence-free survival was similar between all AAD groups (69.7% vs. 67.2% vs. 71.9% vs. 80.0%, p = 0.439). About half of all recurrences occurred during the first month. There was no difference in any of the secondary outcomes, although the amiodarone group showed a trend toward more non-pharmacological rhythm control. AAD type was not associated with recurrence in multivariate analysis. In this study, half of all patients received amiodarone after electrical cardioversion. Flecainide, propafenone, amiodarone, and dronedarone showed similar efficacies for maintaining SR after electrical cardioversion. Thus, it might be reasonable to reconsider amiodarone use after cardioversion, since it did not show superior efficacy to the other drugs considered and is associated with potential side effects.